Uji Aktivitas Enzim Superoksida Dismutase (SOD) Ekstrak Daun Jambu Biji (Psidium guajava L.) dengan Metode Water Soluble Tetrazolium Salt-1 - Mandasari, Mitha Oktavia; Indrayati, Ana; Purwaningsih, Desi (Universitas Islam Indonesia, 2025)
Background: Antioxidants are compounds that inhibit cell damage caused by free radicals. Antioxidant enzymes include superoxide dismutase (SOD), glutathione, and catalase. SOD protects cells against free radicals implicated in various diseases. The guava plant (Psidium guajava L.) is known to possess SOD activity.Objective: This research was performed to determine the activity of the superoxide dismutase enzyme in guava leaf extract (Psidium guajava L.) with ammonium sulfate concentrations of 25, 50, and 75%.Methods: Guava leaves were extracted using phosphate buffer and centrifugation. The superoxide dismutase (SOD) enzyme was then purified using ammonium sulfate at concentrations of 25, 50, and 75%. The amount of protein was measured with the Lowry method, and the activity of the SOD enzyme was tested using the WST-1 assay to find out how much it was inhibited. The resulting data were statistically analyzed using one-way ANOVA.Results: Guava leaf extract exhibits SOD enzyme activity. The total protein content of the crude guava leaf extract and the extracts purified with 25, 50, and 75% ammonium sulfate were 9.683, 6.958, 8.842, and 11.269 mg/mL, respectively. The corresponding percent inhibition values were 69.652, 35.323, 61.69, and 79.104%. The 75% ammonium sulfate concentration yielded the highest percent inhibition.Conclusion: Guava leaf extract exhibits SOD enzyme activity, with the highest percent inhibition observed at an ammonium sulfate concentration of 75%.